EXERGETIC ANALYSIS OF AN INTERNAL COMBUSTION ENGINE RUNNING ON E22 AND E100 - Rovai, F. F.; Mady, C. E. (Revista de Engenharia Térmica, 2022)
The internal combustion engine performance enhancement is a widely explored subject. Additionally, to pollutant emissions attention, reducing fuel consumption and consequently the greenhouse gas emissions is one of the leading research and development drivers for the future of the engines industry. As the technologies to increase global engine efficiency are becoming less promising (already reaching improvement limits), the next round would be developing technologies capable of recovering the energy rejected to the environment, especially by cooling and exhaust systems. The internal combustion engine efficiency is mainly assessed by its global efficiency, which consists of an energy balance. The exergy analysis enhances the classic energy analysis from the concept of maximum possible work, including the rejected energy, consisting of a handy tool for the feasibility study of energy recovery systems. This article presents and contrasts the energy and the exergy analyses of a flex-fuel internal combustion engine running on its top global efficiency condition. The boundary fuels are hydrous ethanol (E100) and gasoline blend (E22), available fuels in Brazil. The hydrous ethanol fuel properties (octane number, air-fuel ratio, and vaporization enthalpy) theoretically result in higher energetic engine efficiency than E22 in the same engine hardware, with a fixed compression ratio. Preliminary results of this study point 4,5% higher global engine efficiency running on E100 compared to E22. The higher engine energy efficiency running on E100 than E22 does not happen in the Second Law analysis. The classic exergetic efficiency, based on engine brake power, is similar for E22 and E100. The maximum exergetic efficiency, based on destroyed exergy, is 4,1% higher for E22 compared to E100. The estimation and comparison of the exergy rejected to the cooling and the exhaust systems according to the boundary fuel (about 21 kW on average in this case), is fundamental to assess the potential and the availability of any recovery system eventually implemented in the internal combustion engine.